2020
DOI: 10.21203/rs.3.rs-53378/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparison of bispectral index and patient state index during sevoflurane anesthesia in children: a prospective observational study

Abstract: Background: Cortical electroencephalography (EEG)-based devices are used to monitor the depth of anesthesia. In this study, we compared the values of bispectral index (BIS) and patient state index (PSI) during sevoflurane anesthesia in children. The ability/accuracy of BIS and PSI to predict the steady and recovery state of anesthesia was evaluated based on prediction probability (Pk) values and the secondary outcomes were agreement and correlation of two monitors. Methods: Fifty children (3-12 years old) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Sang–Hwan et al . [ 20 ] in their study, had demonstrated that BIS and PSI can both be used to monitor the maintenance state and recovery state.…”
Section: Discussionmentioning
confidence: 99%
“…Sang–Hwan et al . [ 20 ] in their study, had demonstrated that BIS and PSI can both be used to monitor the maintenance state and recovery state.…”
Section: Discussionmentioning
confidence: 99%